VD_FINDINFO HC / 2013 / 424 vom 28. Juni 2013 - VD Tribunal cantonal (2013)
MESURE PROVISIONNELLE, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE, CONCUBINAGE | 176 al. 1 CC, 179 CC, 276 CPC (CH), 308 CPC (CH), 318 al. 1 let. b CPC (CH)